Blue economy: Emerging global trends and India's multilateral cooperation. (2nd January 2020) - Upadhyay, Dinoj K.; Mishra, Manoranjan
ABSTRACT: Blue economy, which promotes sustainable usages of ocean resources for economic growth and development, as well as preservation of the health of ocean ecosystem, has become a crucial element of the broader ecosystem of sustainable and inclusive development. The desire to sustainably harness the potential of ocean and marine resources has been amply visible at the national and global level. Technological innovations, investment and multilateral cooperation have further been facilitating progress in the sectors of blue economy. Placed in a central position in the Indian Ocean and with a vast exclusive economic zone (EEZ), India has substantial potential for tapping marine resources and blue economy could emerge as the paradigm of development in the future. New Delhi has taken many initiatives to promote blue economy activities and development of modern infrastructure for greater connectivity, international collaboration and trade facilitation. Further, it is seeking wider multilateral cooperation in areas of financing, technology transfer, capacity building and knowledge sharing. This paper underlines the importance of blue economy in a broader framework of sustainable development and analyses India's foreign policy orientation towards blue economy. Finally, it also discusses cooperation between India and European countries in the sectors of blue economy.